2005
DOI: 10.1124/jpet.105.083428
|View full text |Cite
|
Sign up to set email alerts
|

θ Isoform of Protein Kinase C Alters Barrier Function in Intestinal Epithelium through Modulation of Distinct Claudin Isotypes: A Novel Mechanism for Regulation of Permeability

Abstract: Using monolayers of intestinal Caco-2 cells, we discovered that the isoform of protein kinase C (PKC), a member of the "novel" subfamily of PKC isoforms, is required for monolayer barrier function. However, the mechanisms underlying this novel effect remain largely unknown. Here, we sought to determine whether the mechanism by which PKC-disrupts monolayer permeability and dynamics in intestinal epithelium involves PKC--induced alterations in claudin isotypes. We used cell clones that we recently developed, clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 49 publications
2
49
0
Order By: Relevance
“…In the current study, we have assessed and determined changes in cortical endothelial cell distribution and expression of nPKC-y, and aPKC-z isozymes in isolated microvessels and membrane-and cytosolic-enriched fractions, induced by Hx and HR. The selection of these PKC isozymes was based on reports that these two isozymes are associated with TJ proteins (GonzalezMariscal et al, 2008), previous studies in our laboratory (Fleegal et al, 2005) and a recent report by Banan et al (2007) showing an association between PKC-y and claudin-5 in the intestine. We have shown increased expression and activation of nPKC-y and aPKC-z after Hx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, we have assessed and determined changes in cortical endothelial cell distribution and expression of nPKC-y, and aPKC-z isozymes in isolated microvessels and membrane-and cytosolic-enriched fractions, induced by Hx and HR. The selection of these PKC isozymes was based on reports that these two isozymes are associated with TJ proteins (GonzalezMariscal et al, 2008), previous studies in our laboratory (Fleegal et al, 2005) and a recent report by Banan et al (2007) showing an association between PKC-y and claudin-5 in the intestine. We have shown increased expression and activation of nPKC-y and aPKC-z after Hx.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence studies have shown PKC isozymes to colocalize with ZO-1 in Madin-Darby canine kidney and human colon adenocarcinoma cells (Dodane and Kachar, 1996). In other studies, activation of nPKC-y was reported to affect intestinal epithelial barrier function through modulation of claudin isotypes (Banan et al, 2004(Banan et al, , 2007.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some investigations have shown modulation of claudin-4 by aPKC [30] and PKCθ [34]. In Caco-2 cells, constitutively active PKCθ is necessary to maintain barrier function and this process involves the phosphorylation of claudin-1 and -4 [34].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have demonstrated the involvement of various kinases in the phosphorylation and regulation of claudin proteins [29][30][31][32][33][34][35][36][37], and we have recently shown that phosphorylation of claudin-3 by PKA can affect TJ properties in ovarian cancer cells [38]. Protein kinase C (PKC) isoforms are present in ovarian cancer and are known to modulate TJ function by phosphorylation of the proteins in the complex [24,34,[39][40][41][42][43], but it is unclear whether PKC can directly phosphorylate and regulate claudin proteins. We have previously shown that claudin-4 can be phosphorylated in ovarian cancer cells upon 12-OTetradecanoylophorbol-13-acetate (TPA) stimulation [38], but the exact PKC isoforms involved, the phosphorylation sites on claudin-4, and the consequences of this phosphorylation have remained unknown.…”
Section: Introductionmentioning
confidence: 99%